Hypocholesterolemic effect of acacia and citrus honeys on cholesterol induced sprague dawley rats - Hussain, Muhammad Bilal; Ahmad, Rabia Shabir; Arshad, Muhammad Umair; Imran, Ali; Imran, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2021)
During the last decade, scientific investigations have put more focus on diet based therapies to prevent numerous maladies especially hypercholesterolemia and related disorders. Current project was designed to discover the nutraceutical worth of natural unifloral honeys from Acacia nilotica (Desi Kikar) and Citrus limetta (Mosambi) against hypercholesterolemia. Initially both honey varieties were analyzed for TPC and TFC, followed by DPPH and FRAP assays. Afterwards, honey drinks were prepared using different concentrations of Acacia and Citrus honeys (10:20:30 g/250 mL water) and were tested in experimental rat model. Initially the rats were provided with high cholesterol diet (2%) to induce hypercholesterolemia, which were then provided with honey drinks for 8 weeks. These were monitored regularly for feed and water intake and weekly for body weight gain. The blood samples for total cholesterol, LDL, HDL, triglyceride levels as well as safety assessment tests were analyzed at the intervals of 0, 28, and 56 days, which showed that Acacia honey was better in terms of antioxidant potential (DPPH, FRAP, and TPC) than the Citrus honey. Feed and drink intakes along with body weight gain showed significant effect among all the experimental groups. Substantial reduction in cholesterol, LDL and triglycerides was observed in G3 (213.82±3.36 to 183.95±3.02 mg/dL), (150.05±2.30 to 125.44±3.32 mg/dL) and (163.24±4.87 to 133.64±4.75 mg/dL), respectively, from 0 to 56th day. Liver and kidney functioning values decreased within the normal range. Owing to strong antioxidant potential, Acacia honey was proved to be more effective in controlling hypercholesterolemia than the Citrus honey.